‘Augustus’: the first emperor of Rome - Cruz, Nathália Queiroz Mariano (Romanitas - Revista de Estudos Grecolatinos, 2015)
Review of: GOLDSWORTHY, A. Augustus: first Emperor of Rome. New Haven: Yale University Press, 2014. 624 p.